A new business model for encouraging the adoption of electric vehicles in the absence of policy support. (1st February 2019) - Nian, Victor; Hari, M.P.; Yuan, Jun
Highlights: A new business model for electric vehicles without policy support is developed. The model is inspired by post-paid telecom mobile device purchase discount. The model makes electric vehicles cost competitive in the worst market environment. The model can benefit all stakeholders in the ecosystem of electric vehicles. Abstract: The developments in electric vehicles (EVs) are driven by the need for cleaner and more efficient road transport. Despite the benefits of electrifying the transport sector, both EVs and internal combustion engine vehicles add to road congestion. Major cities around the world have thus employed vehicle control measures to rein the growth rate of vehicle populations. In the case of Singapore, heavy taxes are levied onto the purchase price of all vehicles registered and sold in the country making it literally the most expensive city to own a car. EVs are also penalized under the taxation scheme implemented in Singapore. The vehicle taxation schemes and the absence of incentive measures for EVs make Singapore the worst-case market environment for EV adoption. Through a dissection of Singapore's vehicle control measures, a new business model is proposed for promoting the adoption of EVs under Singapore's market environment. The proposed business model, inspired by telecommunication companies' mobile phone purchase contract aims at reducing the upfront purchase price of EVs via quasi-discount by vehicle dealers without affecting the transport sector tax revenues. Under a contractual arrangement over usage and electricity tariff managed by vehicle dealers, EV buyers effectively pay back the discounted upfront cost over a fixed period of time. Through an examination over a range of repayment periods and their impacts on costs, we find that the repayment period has virtually no impact on the total cost of vehicle ownership. We further contemplate that the same business model can be applicable to all cities in promoting the adoption of EVs without affecting the existing policy infrastructure.